Formation and metabolism of 6-(1-acetol)-8-(1-acetol)-rutin in foods and in vivo, and their cytotoxicity - Chen, Min; Liu, Pengzhan; Zhou, Hua; Huang, Caihuan; Zhai, Weiye; Xiao, Yuantao; Ou, Juanying; He, Jun; El-Nezami, Hani; Zheng, Jie (Frontiers in Nutrition, 2022)
Methylglyoxal (MGO) is a highly reactive precursor which forms advanced glycation end-products (AGEs) in vivo, which lead to metabolic syndrome and chronic diseases. It is also a precursor of various carcinogens, including acrylamide and methylimidazole, in thermally processed foods. Rutin could efficiently scavenge MGO by the formation of various adducts. However, the metabolism and safety concerns of the derived adducts were paid less attention to. In this study, the optical isomers of di-MGO adducts of rutin, namely 6-(1-acetol)-8-(1-acetol)-rutin, were identified in foods and in vivo. After oral administration of rutin (100 mg/kg BW), these compounds reached the maximum level of 15.80 μg/L in plasma at 15 min, and decreased sharply under the quantitative level in 30 min. They were detected only in trace levels in kidney and fecal samples, while their corresponding oxidized adducts with dione structures presented as the predominant adducts in kidney, heart, and brain tissues, as well as in urine and feces. These results indicated that the unoxidized rutin-MGO adducts formed immediately after rutin ingestion might easily underwent oxidation, and finally deposited in tissues and excreted from the body in the oxidized forms. The formation of 6-(1-acetol)-8-(1-acetol)-rutin significantly mitigated the cytotoxicity of MGO against human gastric epithelial (GES-1), human colon carcinoma (Caco-2), and human umbilical vein endothelial (HUVEC) cells, which indicated that rutin has the potential to be applied as a safe and effective MGO scavenger and detoxifier, and AGEs inhibitor.